Burnout and job satisfaction among secondary school counselors in district of Johor Bahru - Neo, Lay Geat (2013)
The purpose of this study was to investigate the level of burnout, level of job satisfaction, and demographic factors in term of subscales for burnout among secondary school counsellors in district of Johor Bahru as well as correlation between subscales of burnout with subscale of job satisfaction. This study is conducted among ninety-seven secondary school counsellors through random systemic sampling. In this study, questionnaire were used. Maslach Burnout Inventory (MBI) is used to measure the level of burnout, while Job Descriptive Index(JDI) is used to measure the level of job satisfaction. The results showed that majority of high school counsellors have moderate job satisfaction with a low satisfaction subscale salary and opportunities for promotion. The results also indicated that majority of them have low level of burnout at all subscales ( Depersonalization, emotional exhaustion and Personal accomplishment). Results also showed that there is significant differences between Personal Accomplishment (PP) with year of service, while no significant difference between burnout subscales with other demographic factors (marital status and gender). Meanwhile Pearson correlation analysis showed that there was only a weak significant relationship at all subscale of burnout at significance level p < .05. Lastly, implication of the study ,suggestion to improve job satisfaction and reduce burnout are discussed.